Digitalization of money, reorganization of payment systems, and new services in Latin American territories - Iamonti, Victor Zuliani (Geografares, 2026)
In recent decades, Latin American territories have undergone an accelerated transformation in their financial dynamics, driven by the digitalization of money and the expansion of new financial services and instruments, requiring a profound reorganization of national payment systems. Understanding money as one of the forms of geographical space and, as such, imbued with technical and political dimensions, this study aims to examine how these processes take shape in particular ways across Latin American countries, marked by historical legacies, institutional frameworks, structural vulnerabilities, and contradictions, but also by the production of materialities, networks, and services that are reshaping urban dynamics..
Keywords: digitalization; financialization; Latin America